2013
DOI: 10.1177/1744629513483523
|View full text |Cite
|
Sign up to set email alerts
|

Parenting with disabilities

Abstract: This article reports on the initial stages of implementing an Australian-based education programme for parents with intellectual disabilities (IDs) in Sweden. The clinical utility of the programme, Parenting Young Children (PYC), in the new country context is explored through Swedish professionals' experiences in learning and using it. Study participants found PYC well suited for use in their working environment. Most of them reported the programme to have strengthened their work with parents. The programme wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…In line with previous research, participants argued that workers often lack the training and practice tools they need to effectively support parents with intellectual disability and their families (Starke et al, 2013, Strnadova, et al, 2017). Participants highlighted the need for training and support to develop capabilities for reflective practice, relationship building and research utilisation.…”
Section: Discussionsupporting
confidence: 55%
“…In line with previous research, participants argued that workers often lack the training and practice tools they need to effectively support parents with intellectual disability and their families (Starke et al, 2013, Strnadova, et al, 2017). Participants highlighted the need for training and support to develop capabilities for reflective practice, relationship building and research utilisation.…”
Section: Discussionsupporting
confidence: 55%
“…The present study examines the experiences of mothers with cognitive limitations who have children in placement, looking at their mothering role after participation in MTA. Previous studies have shown that individual interventions adapted to this target group can be beneficial in increasing parents' ability to manage their situation (Feldman, 1994;Feldman et al, 1999;Starke, 2005;Starke, 2011;Starke et al, 2013;Wade et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge about the support provided for parents with cognitive limitations focuses largely on parents with children living at home (Starke, 2005). It is known that methods adapted to cognitive limitations can improve parental competence in caring, safety and security, feeding, problem-solving, parent-child interaction as well as help the mother to affect the child's behaviour (Feldman, 1994;Feldman, Duchamre, & Case, 1999;Starke, 2011;Starke, Wade, Feldman, & Mildon, 2013;Wade, Llewellyn, & Matthews, 2008). These studies highlight the importance of providing adaptations tailored to each parent, to the cognitive limitations of the parent and to needs the parent experiences as well as the importance of doing so in settings where the new skills are needed.…”
Section: Support For Parents With Cognitive Limitationsmentioning
confidence: 99%
“…Bien que la recherche ait permis d'identifier certaines mesures favorisant le développement des habiletés parentales chez les parents ayant une DI/LI, il demeure difficile de traduire ces savoirs en interventions efficaces (Starke, Wade, Feldman et Mildon, 2013;Wade et al, 2008). Encore faut-il que les professionnels bénéficient de conditions de travail qui facilitent la mise en oeuvre de ces savoirs.…”
Section: Facteurs Relatifs Aux Interactions Parentsintervenantsunclassified